2021
DOI: 10.3390/ijerph18158014
|View full text |Cite
|
Sign up to set email alerts
|

Wayfinding of Firefighters in Dark and Complex Environments

Abstract: Firefighters searching in dark and complex environments might lose their orientation and endanger themselves at the fireground. This study conducted experiments in the Training Facility of the New Taipei City Fire Department (NTFD), Taiwan. The objective of the experiments was to analyze the profile of each firefighter by a 13-factor self-report survey and their wayfinding time in dark and complex environments (DCEs). The results showed that age might be a marginally significant factor, and fear of confinement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Demographic factors [18] • Wayfinding-induced stress and its correlation with the age of wayfarers [19] • Working memory has an effect on wayfinding performance [41] • Effect of age and fear of confinement on wayfinding [42] • Gender effects on wayfinding performance [43] [44] [37] • Level of education effects on wayfinding performance • Native language effects on wayfinding performance Spatial knowledge [22] • Spatial learning association with wayfinding performance Theories of Human spatial perception can be described as a group of theories of perception that attempted to explain the mechanisms in which the perception of sensory information occurs; these theories also touched on the mechanisms involved in the processes of information acquisition [21]. Falling under this category of theories are Gestalt theory, the theory of direct perception, template theory, and constructivist theory [7].…”
Section: Factor Classification References Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic factors [18] • Wayfinding-induced stress and its correlation with the age of wayfarers [19] • Working memory has an effect on wayfinding performance [41] • Effect of age and fear of confinement on wayfinding [42] • Gender effects on wayfinding performance [43] [44] [37] • Level of education effects on wayfinding performance • Native language effects on wayfinding performance Spatial knowledge [22] • Spatial learning association with wayfinding performance Theories of Human spatial perception can be described as a group of theories of perception that attempted to explain the mechanisms in which the perception of sensory information occurs; these theories also touched on the mechanisms involved in the processes of information acquisition [21]. Falling under this category of theories are Gestalt theory, the theory of direct perception, template theory, and constructivist theory [7].…”
Section: Factor Classification References Remarksmentioning
confidence: 99%
“…When this Weak influence expresses itself during the actual travel of a navigating person, it is not only Weak but also Synchronous. This type of wayfinding can be best represented in studies in which participants were finding their destinations within a space by incorporating verbal communication as a means of communication [88][89][90] or by mimicking other people's wayfinding behavior [41,87].…”
Section: Synchronous Social Wayfindingmentioning
confidence: 99%
“…Currently, stationary active dynamic signage systems are the standard for indicating the direction in which people should move during an emergency [3][4][5][6][7][8][9]. Since these tend to be mounted on a wall or ceiling [10], smoke can easily affect visual guidance during a fire [11][12][13]. In fact, some research has shown that such systems are not an optimal solution for evacuation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the smoke control performance of building doors has been specified in various countries [3][4][5][6][7][8][9], requiring qualified smoke control doors to provide smoke control capabilities under both medium-temperature and ambient-temperature conditions. As a consequence of the complexity of fire scenarios, ambient-temperature smoke may also be life threatening [10]. For example, if a source of fire is relatively distant from a door, the temperature of the smoke near the door may be relatively low or even comparable to ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%